2009
DOI: 10.1007/s00464-009-0371-0
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopy-assisted pancreas- and spleen-preserving total gastrectomy for gastric cancer as compared with open total gastrectomy

Abstract: LATG is associated with less severe complications and better postoperative quality of life than OTG. We believe that LATG is a safe, useful, and less invasive alternative for the treatment of gastric cancer located in the upper or middle third of the stomach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 21 publications
4
61
1
Order By: Relevance
“…In many of these comparative studies, longer operation times, less blood loss, and equal numbers of dissected lymph nodes were observed in the LTG group compared with the OTG group [45][46][47]. Obviously, these outcomes will have been dependent on the extent of lymph node dissection, whether multiple organ resections were performed, and the skill of the surgeons in each study.…”
Section: Reconstruction Methods After Laparoscopic Total Gastrectomymentioning
confidence: 99%
See 1 more Smart Citation
“…In many of these comparative studies, longer operation times, less blood loss, and equal numbers of dissected lymph nodes were observed in the LTG group compared with the OTG group [45][46][47]. Obviously, these outcomes will have been dependent on the extent of lymph node dissection, whether multiple organ resections were performed, and the skill of the surgeons in each study.…”
Section: Reconstruction Methods After Laparoscopic Total Gastrectomymentioning
confidence: 99%
“…Many studies reported that there were no significant differences in the incidence of complications between the LTG and OTG groups [45][46][47]51]. Among anastomosis-related complications in the LTG group, leakage at the site of esophagojejunostomy was observed in 0.9-8.5 % of patients, leakage at the duodenal stump was seen in 1.0-3.4 % of patients, stricture at the site of esophagojejunostomy was seen in 0-9.0 % of patients, intraluminal bleeding was seen in 0-7.6 % of patients, and ileus or stasis was seen in 0-3.3 % of patients [19,23].…”
Section: Postoperative Complicationsmentioning
confidence: 99%
“…This section discusses the indications and short-term outcomes. Several reports, including subset analyses, of case comparison studies between open total gastrectomy and laparoscopic total gastrectomy have been published regarding indications for laparoscopic total gastrectomy (27)(28)(29)(30)(31)34). However, only several dozens of the laparoscopic total gastrectomy cases were investigated in any of the report, and studies from Japan and Korea are limited to patients with early gastric cancer.…”
Section: Evidence Regarding Laparoscopic Total Gastrectomymentioning
confidence: 99%
“…Regarding post-operative short-term outcomes in all reports of case-control studies including subset analyses, laparoscopic total gastrectomy was demonstrated to have a longer surgical duration, but a smaller amount of intraoperative bleeding than open total gastrectomy (27)(28)(29)(30)(31). Several studies have also showed that laparoscopic total gastrectomy resulted in smaller post-operative increases in leukocytes and C-reactive protein (27,28,30), less post-operative pain (28,30) and earlier recovery of intestinal movement (27).…”
Section: Evidence Regarding Laparoscopic Total Gastrectomymentioning
confidence: 99%
“…Some surgeons have reported the use of extracorporeal approaches through mini-laparotomy [7,8], which may spoil the cosmetic benefits of laparoscopic surgery. Another approach involves side-to-side anastomosis using a linear stapler [9,10].…”
Section: Introductionmentioning
confidence: 99%